Enhancing Mathematics Learning Outcomes through Realistic Mathematics Education: Evidence from Classroom Implementation - Siregar, Nuriana Br; Ernidalisma, Ernidalisma; Sumirah, Sumirah (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The aim of this study was to determine whether or not the Realistic Mathematics Education approach had an influence on students' mathematics learning outcomes. Methodology: This study is a quasi-experimental study using a nonequivalent control group design consisting of 38 students in the experimental class and 35 students in the control class with a purposive sampling technique. The data collection technique used was a pretest and posttest. Main Findings: The student learning outcomes test after being given treatment was analyzed using descriptive statistical analysis and inferential statistical analysis. The results showed a difference between the mathematics learning outcomes of students in the experimental class and students in the control class with tcount > ttable (tcount = 1.91; ttable = 1.666). Based on this, it can be concluded that there is an influence of the Realistic Mathematics Education approach on student learning outcomes. Novelty/Originality of this study: This study provides empirical evidence on the effectiveness of the Realistic Mathematics Education approach through a quasi-experimental, non-equivalent control group design at the classroom level. This study expands existing knowledge by demonstrating measurable differences in learning outcomes using pre-test and post-test analyses, thus strengthening the practical evidence base for implementing Realistic Mathematics Education in real-world learning environments.